Pengaruh Perendaman Plat Resin Akrilik dalam Perasan Buah Jeruk Purut (Citrus Hystrix Dc.) Terhadap Pertumbuhan Jamur Candida Albicans - Septiana, Reinita Fajril; , drg. Noor Hafida Widyastuti, Sp.KG; , drg. Fitria Nur Malita Sari (2015)
Heat cured acrylic resin was a plate and it has micro pores that can absorb water which contain remaining food on teeth, allowed Candida albicans was widely spread on mucosa, causing denture stomatitis. Disinfectant submersion was suggested against fungi growth. Kaffir lime (Citrus hystrix DC.) squeeze was a natural essence with antifungal power, that easy to find and safe for mucosa's structure. This study was conducted to find out the effect of acrylic resin plate submersion into kaffir lime (Citrus hystrix DC.) squeeze against Candida albicans growth. Acrylic resin plates were inoculated with Candida albicans which (10x10x1) mm, 25 samples and divided into 5 groups, 3 groups with different kaffir lime squeeze concentration, 20%, 40%, 60%, a negative control group (aquades) and a positive control group (0.2% chlorhexidine) were submerged into the solution for about 8 hours. The samples were then put into conical tube, attached on vortex mixer for 1 minute and dilluted up to 10-3. Sabouraud agar was used for germination on 37°C 48 hours incubation. Formed fungi were counted for the datas. Data was analized using Kruskal-Wallis and Mann-Whitney post-hoc test. The result showed that there was an effect of acrylic resin plate submersion into kaffir lime (Citrus hystrix DC.) squeeze against Candida albicans growth, while the effect getting better when the concentration was bigger